Seasonal evaluation of the condition factor in a surf-zone assemblage from southeastern Brazil - Santos, Eidi Kikuchi; De Grande, Fernando Rafael [UNESP]; Vaske-Júnior, Teodoro [UNESP] (Boletim do Instituto de Pesca, 2019)
The surf zone is a highly dynamic environment subject to seasonal fluctuations which could impose restrictions to the development of juvenile fish. The allometric condition factor index (K) provides a value of ‘well-being’ for fish, been used to compare populations under different environmental conditions. The aim of this study concerned on evaluate the effect of seasonality on surf-zone juvenile fish’ K. Along two years the K values of the main fish species were analyzed. The temperature and abundance were also reported. We compared data between cold and hot seasons to test the effect of seasonality. A total of 955 individuals were collected, totaling 20 species. Despite the surf zone instability, most fish species showed a stable K regardless of season. We found that the condition factor in neritic Atherinella blackburni, Mugil brevirostris, Trachinotus carolinus and Trachinotus goodei did not vary. Only a demersal species, Menticirrhus littoralis, shown the lowest condition factor in the hot season, coinciding with maximum water temperature. We discussed how the surf zone provides conditions for the development of fish and reinforce the importance of this environment as a breeding site.
Avaliação sazonal do fator de condição em uma assembleia de peixes da zona de arrebentação no sudeste do Brasil
Keywords: Abundance; Demersal; Juvenile; Neritic; Seasons; Temperature